OPEN INNOVATION STRATEGY AND INNOVATION SPEED: BRIDGING THE GAP TO BUSINESS EXCELLENCE - Adedimeji Shoetan (Universitas Kuningan, 2025)
The study focuses on manufacturing and bottling companies, and its goal is to investigate the mediating role between innovation speed and open innovation on business excellence. The specific objective is to research how business strategies affect the degree of openness that is implemented and how open innovation affects the bottom line. A total of 120 replies were received from managers and supervisors in core departments of two Nigerian manufacturing firms: the Nigerian Bottling Company (NBC & Coca-Cola), and Seven-Up Bottling Company, Lagos Plant. Research framework constructs were developed and confirmed, and structural equation modelling was used to test hypotheses regarding the connections being investigated. The results show that open innovation strategy from the dimension of inbound and outbound is evidenced to have a positive impact on business excellence and innovation speed. The study concludes that companies with a focus on innovation are those that put more resources into developing their technical and core competencies. Companies that pursue a diversification strategy tend to rely only on open innovation managerial techniques, whereas companies that prioritize efficiency are more likely to rely on the practice of open innovation, and to an extent, the development of core competencies. These findings are valuable to researchers, industry professionals, and academia.